(untitled) (Journal of Engineering, 2013)
This work predicts the effect of thermal load distribution in polymer melt inside a mold and a die during injection and extrusion processes respectively on the structure properties of final product. Transient thermal and structure models of solidification process for polycarbonate polymer melt in a steel mold and die are studied in this research. Thermal solution obtained according to solidify the melt from 300 to 30Cand Biot number of 16 and 112 respectively for the mold and from 300 to 30 Cand Biot number of 16 for die. Thermal conductivity, and shear and Young Modulus of polycarbonate are temperature depending. Bonded contact between the polycarbonate and the steel surfaces is suggested to transfer the thermal load. The temperatures distribution produces in thermal model importing as load and boundary conditions to solve the structure model. 3D mold and die are built to simulate the thermal and structure behavior using ANSYS 12.1 program. The results show that the temperatures and residual stresses decreases with the distance from the center to surfaces for the mold ,while for the die the temperatures and stresses decreases with the distance from the inlet to the outlet. The temperatures and stresses decreases with the time increasing for both mold and die. Also the thermal strain compatible with the temperatures distribution in the mold and the die. The total deformation concentrated at the left and right edge of polycarbonate in the mold, while starting in the center of the polymer at the outlet and then transfer to the entry of the die with the time increasing.